2010
DOI: 10.1677/jme-10-0046
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow trout somatostatin receptor subtypes SSTR1A, SSTR1B, and SSTR2 differentially activate the extracellular signal-regulated kinase and phosphatidylinositol 3-kinase signaling pathways in transfected cells

Abstract: Previously, we reported that extracellular signal-regulated kinase (ERK) and protein kinase B (Akt), a downstream target of phosphatidylinositol 3-kinase (PI3K), mediated somatostatin (SS) inhibition of GH receptor, IGF1, and IGF1 receptor expression. In this study, we used Chinese hamster ovary-K1 cells that stably transfected individually with trout SS receptors (SSTR1A, SSTR1B, and SSTR2) to elucidate receptor-effector pathway linkages. SS induced ERK and Akt activation in a time-and concentration-related m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…In the rainbow trout, Oncorhynchus mykiss , three sequences have been reported [42,43]. In our additional analysis the two sequences identified as SSTR1a and -1b [43,44] can be correctly identified as two copies of SSTR6 likely resulting from the salmonid fourth tetraploidization (see Additional file 2, Figure S3).…”
Section: Discussionmentioning
confidence: 88%
“…In the rainbow trout, Oncorhynchus mykiss , three sequences have been reported [42,43]. In our additional analysis the two sequences identified as SSTR1a and -1b [43,44] can be correctly identified as two copies of SSTR6 likely resulting from the salmonid fourth tetraploidization (see Additional file 2, Figure S3).…”
Section: Discussionmentioning
confidence: 88%
“…Other research suggests that SSTs are involved in the regulation of growth hormone sensitivity of fish hepatocytes, and can cause a reduction in the levels of GHR expression and IGF-1 biosynthesis and secretion [86,87]. SSTR2 activation is linked to inhibition of pituitary GH release in fish [88]. Additionally, there is an inverse correlation between SST plasma levels and thyroid hormone levels in fish [89].…”
Section: Growth Hormone Inhibiting Hormone (Ghih or Somatostatin Sst)mentioning
confidence: 99%
“…Overexpression of MDR1 leads to membrane p-glycoprotein (p-gp) overexpression, which could decrease the intracellular paclitaxel concentration, and results in the reduced inhibitory effect on tumor cells by paclitaxel [31–42]. Studies have shown that, SSTA can suppress MDR1 expression and reverse drug resistance by inhibiting the PI3K/Akt signal pathway when binding to SSTR1A, SSTRR1B and SSTR2 [21]. In our study, POC treatment significantly decreased the mRNA and protein expressions of MDR1 if compared with other treatment group which was consistent with our previous study in vitro .…”
Section: Discussionmentioning
confidence: 99%